The Confidence Building Measures Between India & Pakistan: A Constructivist View - Rehman, S.; Azam, A.; Hussain, W.; Ahmad, K. M. (The Nucleus, 2018)
Confidence building measure are generally viewed as important agents of change for introducing peace and stability among rival states. Both of the nuclear states of South Asia have undertaken confidence building measures in the post nuclearization scenario but these measures are not actually building confidence between the two states when seeing from the constructivist perspective. The study suggests that confidence building measure may be used for deconstruction if they are focused in changing existing norms, ideas and shared understanding.